O-315 Can targeted workplace wellness initiatives improve menstrual hygiene management in apparel factories?. (14th March 2023) - Joseph, Merlyn; Joseph, Bobby
Abstract : Introduction: Menstrual problems are an important contributor to poor productivity and sickness absenteeism in the garment industry even today. There are several socio-cultural barriers associated with menstruation which has led to a culture of silence surrounding its discussion. Objectives: 1. To assess the baseline knowledge regarding menstrual hygiene management among female employees working in selected apparel manufacturing industries in India. 2. To determine the change in knowledge and practices in menstrual hygiene and management following targeted workplace health trainings at the factories. Method: A before-after study design was followed to include 291 randomly chosen female employees between May-Dec 2022 from 15 apparel manufacturing factories across India. Baseline awareness and practices regarding menstrual hygiene was determined and the employees were provided a 4-module health training on menstrual hygiene management using the peer-peer educator model. Change in knowledge and practices were documented. Z-test of proportion was calculated. Results: Most of the 291 female employees were in the active reproductive age group of 20–35 years of age (78%). Only 122 women(41.9%) were aware about internal reproductive organs and only 31(10.7%) of them know that menstrual blood originated from the uterus. Around 107 women(36.8%) knew about correct menstrual pad usage and disposal. Most women believed menstrual blood to be 'impure' and only 94 (32.3%) of them were aware about newer menstrual products like the reusable cloth pad and menstrual cup. Following the intervention, knowledge regarding reproductive organs, duration of menstruation, correct pad usage and disposal as well as newer menstrual hygiene products showed significant improvement (p<0.01). Conclusions: Low awareness regarding menstrual hygiene management will impact health seeking behaviour and increase presenteeism at the workplace. A well-designed workplace health intervention to create awareness and dispel myths regarding menstruation shall result in adoption of healthy practices and a healthier workforce.